Analisis Makna Semiotika Pada Lirik Lagu Di Ujung Hari Karya Ungu - Masagus Muhammad Okta Fakri; Indrawati Indrawati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
A song is a literary work, almost the same as poetry, but sung. The lyrics of the song Di Ujung Hari are a religious song which contains a message, namely conveying how difficult it is to live during a pandemic, when the earth is being hit by serious problems and humans can help each other, and whatever trials they face are only a test from God Almighty so that their creatures will be better. strong. In conducting this research, library research researchers used descriptive qualitative research methods. Qualitative research methods are often also called naturalistic research methods because the research is carried out in a natural setting. Qualitative research is carried out on natural objects that develop as they are, are not manipulated by scientists, and the presence of scientists does not actually influence the dynamics of these objects. The song being studied is the lyrics of a song entitled "At the End of the Day", which will explain the first stanza explaining human destiny, then the second stanza will explain about togetherness, then the third stanza will explain disaster, then the fourth stanza will tell about giving, then the fifth stanza will explain about test, then the sixth stanza tells about trials and the seventh stanza explains about belief. The results of this research were obtained from the signs contained in the words and sentences used. In the review, the writer got the lyrics of this song by Arlonsy Miraldi, noting that there is naturally a story behind the lyrics of the song, talking about the inspiration for the song, which was inspired when he realized how difficult it was to live during a pandemic when the Earth was facing serious problems.